SHANK3 Downregulation in the Ventral Tegmental Area Accelerates the Extinction of Contextual Associations Induced by Juvenile Non-familiar Conspecific Interaction - Bariselli, Sebastiano; Contestabile, Alessandro; Tzanoulinou, Stamatina; Musardo, Stefano; Bellone, Camilla (Frontiers in Molecular Neuroscience, 2018)
Haploinsufficiency of the SHANK3 gene, encoding for a scaffolding protein located in the postsynaptic density of glutamatergic synapse, has been linked to forms of Autism Spectrum Disorders (ASD). It has been shown that SHANK3 controls the maturation of social reward circuits in the ventral tegmental area (VTA). Whether the impairments in associative learning observed in ASD relate to SHANK3 insufficiency restricted to the reward system is still an open question. Here, we first characterize a social-conditioned place preference (CPP) paradigm based on the direct and free interaction with a juvenile and non-familiar conspecific. In both group- and single-housed C57Bl6/j late adolescence male mice, this CPP protocol promotes the formation of social-induced contextual associations that undergo extinction. Interestingly, the downregulation of Shank3 expression in the VTA altered the habituation to a non-familiar conspecific during conditioning and accelerated the extinction of social-induced conditioned responses. Thus, inspired by the literature on drugs of abuse-induced contextual learning, we propose that acquisition and extinction of CPP might be used as behavioral assays to assess social-induced contextual association and “social-seeking” dysfunctions in animal models of psychiatric disorders.